À margem dos jornais: uma análise de representação das áreas de vulnerabilidade social da Grande Vitória na imprensa capixaba - Ronchi, Ana Carolina (2019)
This dissertation aims to understand how the printed newspapers A Gazeta and A Tribuna represent the areas of social vulnerability of the Metropolitan Region of Grande Vitória, in Espírito Santo. As a snippet of the localities to be analyzed, the Government of the State of Espírito Santo program called “Ocupação Social” was used. Of the 26 localities contemplated by project 18 are located in the Metropolitan Region, being also those analyzed in this research. At first, it starts off from the discussions around the press as a social institution authorized to narrate about the quotidian. Journalism is understood as a producer of content governed by its own dynamics and routines. Then there is the discussion about the formation of territories and territorialities understanding them in this research both physically - with vulnerable neighborhoods - and symbolically - journalism as social narrator. The reflection on territories culminates in the discussion about violence and how the press is responsible for presenting it (and representing it). Lastly, the information obtained through a Content Analysis on the coverage of the newspapers A Gazeta and A Tribuna around the vulnerable neighborhoods in the year 2016 is evidenced. The research indicates that the neighborhoods of social vulnerability are protagonists in the contents about violence in Espírito Santo and that cultural contents about them are almost non-existent. There is also the discussion around the approach of the two newspapers, their similarities and differences in reporting these facts.